Exploring Employee Experiences of Work Stress and Organizational Climate in Shaping Job Satisfaction in Business organization - Sunarsi, Denok (PINISI Discretion Review, 2025)
Work stress and organizational climate are critical factors influencing job satisfaction in business organizations. The increasing demands placed on employees in dynamic business environments make it essential to understand how work stressors and the organizational climate interact to impact employee satisfaction and performance. This study aims to explore the effects of work stress and organizational climate on job satisfaction among employees in business organizations, employing a qualitative research approach. Semi-structured interviews were conducted with employees across various departments to gather in-depth insights into their experiences with work stress, perceptions of organizational climate, and how these factors influence their overall job satisfaction. The thematic analysis of interview data revealed three key findings: first, work stress negatively affects job satisfaction, with employees reporting feelings of frustration and burnout due to heavy workloads and role ambiguity. Second, a positive organizational climate—characterized by open communication, trust, and supportive leadership—was found to buffer the effects of stress, leading to higher levels of job satisfaction. Finally, organizational support, including recognition, career development opportunities, and adequate resources, plays a critical role in enhancing job satisfaction, even in high-stress environments. These findings suggest that organizations should focus on improving both the work climate and the level of support provided to employees in order to reduce stress and enhance overall job satisfaction, thereby fostering a more productive and engaged workforce.